Da'wah Strategy based on the Independence of Santri: THE POWER OF WOMEN - Wiwin Warliah; Novita Dwi Yanti (STAI Terpadu Yogyakarta, 2023)
This study aims to analyze how the da'wah method is carried out at the Nurul Jadid Islamic Boarding School, Paiton, Probolinggo. To improve the continuity of education for the students and the surrounding community, by focusing their studies on da'wah methods carried out by women. This study uses a qualitative descriptive type approach, in which researchers attempt to analyze the da'wah methods carried out by women, through interviews, observation, and documentation. The results of his research show that the da'wah method carried out by Nyai Aisyah Zaini at the Nurul Jadid Islamic Boarding School turned out to have a major influence on the sustainability of education for students and the surrounding community. This can be seen through three aspects; First, the change in morality from negative social morality to a positive direction. Second, cultivate personality mentality and social awareness. Third, creating independent productivity for the students. Apart from being a source of knowledge, it is also a method to keep reminding and spreading the benefits of knowledge by conveying it directly to the object of da'wah.